Establishment of polyethylene‐glycol‐mediated protoplast transformation for Lecanicillium lecanii and development of virulence‐enhanced strains against Aphis gossypii. Issue 10 (19th February 2016) - Zhang, Yan‐Jun; Xie, Ming; Zhang, Xiao‐Lin; Peng, De‐Liang; Yu, Wen‐Bin; Li, Qiang; Li, Qian; Zhao, Jin‐Jin; Zhang, Zhao‐Rong
Abstract: BACKGROUND: Lecanicillium lecanii has been developed as a biopesticide and used in biological control of several agricultural insects. To improve fungal virulence, an optimised polyethylene glycol (PEG)‐mediated protoplast transformation system was established for L. lecanii . Pr1A‐like cuticle‐degrading protease gene ( Cdep1 ) from Beauveria bassiana was transferred into L. lecanii, and its resulting activity against Aphis gossypii was assessed. RESULTS: The optimised protoplast generation yielded 2.5 × 10 8 protoplasts g −1 wet mycelium of fungi, and gave nearly 98% viability and 80% regeneration on plates. Protease activities were increased about fivefold in transformants expressing CDEP1. The median lethal concentration (LC50 ) for transformants expressing CDEP1 was twofold lower than that for the wild type (WT). The median survival time (LT50 ) for transformants expressing CDEP1 was also 14.2% shorter than that for WT, though no significant difference. There were no significant differences in conidial germination as colony growth and conidial yield on plates between transformants expressing CDEP1 and WT. The transformants expressing CDEP1 grew significantly quicker than WT in insects. The transformants expressing CDEP1 were lower in conidial yields on insect cadavers, but insignificantly different from WT. CONCLUSION: The PEG‐mediated protoplast transformation system was effective for L . lecanii, and the expression of CDEP1 significantly enhanced fungal virulence against cotton aphids. © 2016 Society of Chemical Industry